ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PELAPORAN LINGKUNGAN (ENVIRONMENTAL REPORTING) - Aripianti, Faridha; Sudarno, Sudarno (Diponegoro Journal of Accounting, 2015)
The objective of this study is to examine the influance of corporate governance on environmental reporting. Corporate governance structure measured by 4 proxy there are proportion of independent board, institutional ownership, board size, and proportion of female directors. To measure the amount of environmental reporting using the GRI disclosure items. Control variables in this study are firm size as measured by 3 proxy there are total assets, market capitalizations, and operating revenues. Other control variable profitability is measured using ROA (Return on Assets). The population in this study consists of all the entire mining company and basic industry and chemicals listed in BEI in year 2009-2013. The sampling method used in this study is purposive sampling. The criteria of the sample is a company that has an annual report and sustainability report. By doing sampling and processing data, the final amounts of the sample are 47 samples. This study uses linear regression as an analysis technique to examine the hypotheses. The data analysis showed that proportion of independent board have significant positive influence on environmental reporting. Institutional ownership concentration and board size did non significantly affect environmental reporting. While the proportion of female directors have significant negative on environmental reporting.